Don Leonardo, ¡MAGISTER! - Choza, Jacinto (THÉMATA. Revista de Filosofía, 2014)
1. Años de formación de don Leonardo. 2. Director de Estudios de la Facultad de Filosofía y Letras de la Universidad de Navarra. 3. Polo y su filosofía en los 70 y 80. 4. Maestro y consejero. 5. Personalidad. Cualidades y puntos ciegos. 6. Huérfano de don Leonardo. 1. Formative Years of Don Leonardo. 2. Director of Studies of the Faculty of Arts of the University of Navarra. 3. Polo and his philosophy in the 70s and 80s. 4. Teacher and counselor. 5. Personality. attributes and blind spots. 6. Orphan of Don Leonardo.